Virtual screening and biological evaluation of PPARγ antagonists as potential anti-prostate cancer agents. (15th September 2021) - Almahmoud, Suliman; Elix, Catherine C.; Jones, Jeremy O.; Hopkins, Corey R.; Vennerstrom, Jonathan L.; Zhong, Haizhen A.
Graphical abstract: Abstract: The peroxisome proliferator-activated receptor gamma (PPARγ) was identified as an oncogene and it plays a key role in prostate cancer (PC) development and progression. PPARγ antagonists have been shown to inhibit PC cell growth. Herein, we describe a virtual screening-based approach that led to the discovery of novel PPARγ antagonist chemotypes that bind at the allosteric pocket. Arg288, Lys367, and His449 appear to be important for PPARγ antagonist binding.